Genetic diversity analysis and development of molecular markers for the identification of largemouth bass (Micropterus salmoides L.) based on whole-genome re-sequencing - Du, Jinxing; Li, Shengjie; Shao, Jiaqi; Song, Hongmei; Jiang, Peng; Lei, Caixia; Bai, Junjie; Han, Linqiang (Frontiers in Genetics, 2022)
Largemouth bass (Micropterus Salmoides L.) is generally considered to comprise two subspecies, Florida bass (M. floridanus) and Northern Largemouth bass (M. salmoides), which exists biological characteristic differences because of their geographical distribution. In this study, whole-genome resequencing was performed among 10 Florida and 10 Northern largemouth bass, respectively. In total, 999,793 SNPs and 227,797 InDels were finally identified, and 507,401 SNPs (50.75%) and 116,213 InDels (51.01%) were successfully mapped to annotated 18,629 genes and 14,060 genes, respectively. KEGG classification indicated that most of these genes were focused on the pathways including signal transduction, transport and catabolism, and endocrine system. Genetic diversity analysis indicated that Florida largemouth bass had higher genetic diversity than Northern largemouth bass, indicating that the germplasm quality of Northern largemouth bass had markedly reduced in China. To examine the accuracies of the identified markers, 23 SNPs and 8 Indels (the insertions or deletions bases more than 45bp) were randomly selected and detected among Florida largemouth bass, Northern largemouth bass and their F1 hybrids. The detection efficiencies of all the markers were higher than 95%, 19 SNPs and 3 InDels could accurately distinguish the two subspecies and their F1 hybrids with 100% efficiencies. Moreover, the 3 InDel markers could clearly distinguished the two subspecies and their F1 hybrids with a PCR-based agarose gel electrophoresis. In conclusion, our study established a simple PCR-based method for the germplasm identification of largemouth bass, and which will be useful in the germplasm protection, management, and hybridization breeding of largemouth bass.